The impact of major depression on heart rate variability and endothelial dysfunction in patients with stable coronary artery disease - SÜNBÜL, MURAT (ELSEVIER SCIENCE INC, 2017)
Background: Depression is an independent risk factor in cardiovascular diseases. Changes in the cardiac autonomic functions and pro-inflammatory processes are potential biological factors. Endothelial dysfunction plays an important role in the etiopathogenesis of atherosclerosis. Our objective was to evaluate the impact of major depression on heart rate variability and endothelial dysfunction in patients with stable CAD. Methods: The study group included 65 CAD patients with a diagnosis of major depression and 54 CAD patients without major depression. All study population underwent transthoracic echocardiography, measurement of flow mediated dilatation (FMD) and 24-h holter recording for heart rate variability (HRV). Blood samples were drawn to determine the inflammatory parameters. Severity of depressive episode was assessed by Montgomery-Asberg Depression Scale (MADRS). Results: The distribution of age and sex was similar in the patient and control groups (P = 0.715, 0.354, respectively). There was no significant difference in medications used between the groups. Echocardiographic parameters were similar between the groups. Inflammatory parameters were also similar between the groups. HRV parameters were significantly lower in the patient group than controls. The absolute FMD value and percentage FMD were significantly lower in the patient group than controls (P < 0.001). The MADRS score correlated with pNN50 in both groups (P < 0.05), and with FMD in the control group (P < 0.001), even after adjusting for age and gender (P < 0.001). Conclusions: MADRS score was an independent predictor of pNN50 level, percentage and absolute FMD values regardless of age and gender. Clinician should pay more attention for evaluation of depressive patients with CAD. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Major depression; Endothelial dysfunction; Heart rate variability; Inflammation; CARDIOVASCULAR EVENTS; MYOCARDIAL-ISCHEMIA; CARDIAC EVENTS; RISK-FACTOR; INFLAMMATION; ANXIETY; STRESS; ATHEROSCLEROSIS; ASSOCIATION; COAGULATION